Social service delivery and access to financial innovation: The impact of Oportunidades' electronic payment system in Mexico - Serena Masino; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper follows a quasi-experimental research design to assess the impact of the electronic payment system of Mexico's Oportunidades programme. The switch from cash payments to electronic payments delivered via a bank account is found to have implications in terms of reallocation between saving portfolio choices, transaction costs, and coping strategies. The study shows that, following the intervention, participation in informal saving arrangements was reduced, the frequency of remittance reception increased and, when hit by idiosyncratic shocks, beneficiaries of bank accounts were more likely to use savings rather than contracting loans or reducing consumption to cope with the events. The study also reveals impact heterogeneity between rural and urban areas, with important implications for policy and replicability of similar financial innovations in other developing country contexts.
Keywords: D04; D14; G21; O12; 330; financial inclusion; social service delivery; Oportunidades; conditional cash transfers; quasi-experimental design; Mexico